SAT0347 Value of The Doppler-Ultrasonography for The Diagnosis of Temporal Arteritis. (15th July 2016) - Aranda-Valera, C.; García, S.; Monjo, I.; Rodriguez, M.J.; Martin-Mola, E.; De Miguel, E.
Abstract : Background: Temporal Arteritis (TA) is the most common systemic vasculitis in adults. Usually, the diagnosis is based on the American College of Rheumatology (ACR) classification criteria published in 1990 based on the clinical history, physical examination, laboratory information and histological findings in the biopsy. However, according to the literature, the biopsy can be negative in up to 68% of patients with TA and without it the predictive value diminishes considerably. Objectives: Assess the value of Doppler Ultrasonography for the diagnosis of TA, compared with ACR criteria and biopsy, using the definitive clinical diagnosis of the patient as gold standard. Methods: A retrospective observational, descriptive and analytical study was made, reviewing the clinical history of the patients who had an ultrasound scan of the temporal artery performed in our hospital on suspicion of TA. The standard exploration consists of the bilateral examination of the temporal superficial artery, with its common trunks and the frontal and parietal branches. In the case of diagnostic doubt, the exploration is extended to the occipital arteries and/or axilares. The ultrasound scans were realized and reported by the same person to avoid bias. The variables registered were age and sex, the presence or absence of ACR criteria, VSG value, the final diagnosis and the results of the biopsy and the ultrasound examination as well as the number of affected branches. The statistical analysis was realized by means of the software program SPSS Statistics version 20.0. Results: Of the 451 patients studied, 399 were women and 52 men (88.5% vs 11.5%), with a mean age of 81. Two hundred fifty six patients (58, 8%) had a definite diagnosis of TA while 195 (43, 2%) presented other diagnoses. Two hundred forty patients (55.79%) fulfilled ACR criteria and 211 did not (46, 78%). Of the 166 biopsies, 54 (32, 53%) were positive. The validity (sensitivity and specificity) and security (positive predictive value [PPV], negative predictive value [NPV], Likelihood Ratio [LR] + and LR -) of diagnostic tests used were as follows: Conclusions: Doppler Ultrasonography shows great validity and safety as a diagnostic test of TA, being in addition, a cheaper and less harsh technique than the biopsy.For this reason its use in clinical practice should be considered a diagnostic option of the first line in the diagnosis of this disease. Disclosure of Interest: None declared